Variation for Composition and Quality in a Collection of the Resilient Mediterranean ‘de penjar’ Long Shelf-Life Tomato Under High and Low N Fertilization Levels - Rosa-Martínez, Elena; Adalid, Ana M.; Alvarado, Luis E.; Burguet, Resurrección; García-Martínez, María D.; Pereira-Dias, Leandro; Casanova, Cristina; Soler, Elena; Figàs, María R.; Plazas, Mariola; Prohens, Jaime; Soler, Salvador (Frontiers in Plant Science, 2021)
The ‘de penjar’ tomato (Solanum lycopersicum L.) is a group of local varieties from the Spanish Mediterranean region carrying the alc mutation, which provides long shelf-life. Their evolution under low input management practices has led to the selection of resilient genotypes to adverse conditions. Here we present the first evaluation on nutritional fruit composition of a collection of 44 varieties of ‘de penjar’ tomato under two N fertilization levels, provided by doses of manure equivalent to 162 kg N ha-1 in the high N treatment and 49 kg N ha-1 in the low N treatment. Twenty-seven fruit composition and quality traits, as well as plant yield and SPAD value, were evaluated. A large variation was observed, with lycopene being the composition trait with the highest relative range of variation (over 4-fold) under both N treatments, and significant differences among varieties were detected for all traits. While yield and most quality traits were not affected by the reduction in N fertilization, fruits from the low N treatment had, on average, higher values for hue (5.9%) and lower for fructose (-11.5%), glucose (-15.8%) and total sweetness index (-12.9%). In addition, lycopene and β-carotene presented a strongly significant genotype × N input interaction. Local varieties had higher values than commercial varieties for traits related to the ratio of sweetness to acidity and for vitamin C, which reinforces the appreciation for their organoleptic and nutritional quality. Highest yielding varieties under both conditions displayed wide variation in the composition and quality profiles, which may allow the selection of specific ideotypes with high quality under low N conditions. These results revealed the potential of ‘de penjar’ varieties as a genetic resource in breeding for low N inputs and improving the organoleptic and nutritional tomato fruit quality.